Power Tracing Monitoring incorporating Optimal Reactive Power Dispatch - Fikri Ruslan, Nabil; Musirin, Ismail; Khairuzzaman Mohamad Zamani, Mohamad; Murtadha Othman, Muhammad; Abdul Hamid, Zulkiffli; Abadi Baharuddin, Zikri; Azura Md Ghani, Nor (International Journal of Engineering and Technology, 2018)
General power flow studies do not manage to trace the contributors by generators on power losses in the whole power transmission system. Thus, power tracing approach is utilized to address this issue. Power tracing is a termed used to describe the contributors for the power losses dissipated on the transmission line. The traditional technique made use the knowledge of circuit analysis such as cut set theory. However, there was no element of optimization which can help to achieve the optimal solution. This paper presents the power tracing monitoring during voltage stability improvement process, implemented by optimal reactive power dispatch. In this study, the impact of power tracing on voltage stability variation was investigated. Evolutionary Programming (EP) was developed and utilized to incorporate power tracing, along with voltage stability improvement. A pre-developed scalar voltage stability index was incorporated to indicate the voltage stability condition. On the other hand, the voltage stability initiative was conducted via the optimal reactive power dispatch. The power tracing was monitored for both; the pre-optimization and post-optimization scenarios. Small system model was tested to realize the power tracing phenomenon, which is rather rare study in power system community. Results on power tracing obtained during the pre- and post-optimal reactive power dispatch revealed that not all generators will involve in the contribution on the total transmission loss in the system. This can be beneficial to power system operators for allocating the cost without discrimination in the long run.Â Â Â